2014
DOI: 10.3109/01443615.2014.958145
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of preconception care among women and men: A study from Jordan

Abstract: The objective of this study was to examine awareness of Jordanian married women and men of preconception care. A total of 763 (537 women and 226 men) Jordanians who attended maternal and child healthcare centres in a city, in the centre of Jordan, were included in the current study. The Health before Pregnancy Questionnaire was used to collect the data from participants, while they waited to be seen by the healthcare provider in the health centres. Family history of chronic disorders, 1st-degree consanguineous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 15 publications
7
44
7
Order By: Relevance
“…Whereas it is consistent with study done in Kelantan, Malaysia is (51.9%) (14) and in Qatar is (53.7 %) (23). However, this fining is lower than the study done in Canada is 70%(24),Jordan is (85%) (25),British Colombia is 71%(26), Saudi Arabia is (84.6%) (27) and in the USA among low income Mexican American group is (76%) (28).The possible explanation could be low level of knowledge due to health sector infrastructure difference, socioeconomic difference, lack of health wellness clinic in the study area, lack of preconception service across the country ,lack of promotion on preconception care by mass media, and low commitment of health care providers due to high load of clients.…”
Section: Resultssupporting
confidence: 88%
“…Whereas it is consistent with study done in Kelantan, Malaysia is (51.9%) (14) and in Qatar is (53.7 %) (23). However, this fining is lower than the study done in Canada is 70%(24),Jordan is (85%) (25),British Colombia is 71%(26), Saudi Arabia is (84.6%) (27) and in the USA among low income Mexican American group is (76%) (28).The possible explanation could be low level of knowledge due to health sector infrastructure difference, socioeconomic difference, lack of health wellness clinic in the study area, lack of preconception service across the country ,lack of promotion on preconception care by mass media, and low commitment of health care providers due to high load of clients.…”
Section: Resultssupporting
confidence: 88%
“…However, this finding is not consistent with studies done in Jordan, Nepal and Ghana [18, 20, 27]. This might be due to the fact that education improves communication with partner, women’s status in the community and the influence of education on women’s decision making skill to search source of information.…”
Section: Discussioncontrasting
confidence: 77%
“…The highest knowledge in this study might be due to the fact that there were varied in time and large and representative sample size, which make the study comprehensive. However, it is significantly lower than the findings from Saudi Arabia (37.9%), Jordan (85%) [19, 20], Egyptian (76%) and Arabian (51%) mothers [21]. The low knowledge level in this study might be due to the relative low media coverage in Ethiopia, which showed there is a need to broaden media coverage in the country.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Different articles show that the lifelong medical and socioeconomic consequences of NTDs in affected children are well known to be worse in low-resource settings [13, 21, 22]. Studies done in developed countries such as Canada, Lebanon, and the Netherlands figured out that knowledge on preconception folic acid supplementation was 81.0%, 71.9%, 53.3%, and 36.8%, respectively [23–26]. But based on different studies done in developing countries such as Nigeria, Jordan, and Pakistan, women's knowledge on preconception folic acid supplementation was 25.5%, 21.2%, and 6.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%